The Art of Systems Thinking : - O'Connor, Joseph (Thorsons, 1997)
NLP (Neuro-linguistic programming)trainers and authors O'Connor and McDermott unlock the mysteries of systems thinking and offer practical suggestions, exercises, and tips.